2006
DOI: 10.1002/neu.20241
|View full text |Cite
|
Sign up to set email alerts
|

Role of all‐trans retinoic acid in neurite outgrowth and axonal elongation

Abstract: The vitamin A metabolite, all-trans retinoic acid (atRA) plays essential roles in nervous system development, including neuronal patterning, survival, and neurite outgrowth. Our understanding of how the vitamin A acid functions in neurite outgrowth comes largely from cultured embryonic neurons and model neuronal cell systems including human neuroblastoma cells. Specifically, atRA has been shown to increase neurite outgrowth from embryonic DRG, sympathetic, spinal cord, and olfactory receptor neurons, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
129
2
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(145 citation statements)
references
References 179 publications
(188 reference statements)
9
129
2
5
Order By: Relevance
“…26,27) On the other hand, retinoic acid (RA), an active metabolite of vitamin A, is known to play important roles in nervous system development, including neuronal differentiation, patterning, and outgrowth. 28) In particular, RA is known to induce neurite outgrowth from the spinal cord, dorsal root ganglia neurons, and neuroblastoma cells. [29][30][31] Previous reports have demonstrated that one mechanism whereby RA regulates neuronal outgrowth is by modulation of the expression of neurotrophin receptors, including TrkA and p75 NTR , 30,32) but our understanding of the mechanisms involved in the control of neuronal differentiation and outgrowth by RA remains limited.…”
Section: Virtual Cloning Of Gde2 and It's Physiological Roles Inmentioning
confidence: 99%
“…26,27) On the other hand, retinoic acid (RA), an active metabolite of vitamin A, is known to play important roles in nervous system development, including neuronal differentiation, patterning, and outgrowth. 28) In particular, RA is known to induce neurite outgrowth from the spinal cord, dorsal root ganglia neurons, and neuroblastoma cells. [29][30][31] Previous reports have demonstrated that one mechanism whereby RA regulates neuronal outgrowth is by modulation of the expression of neurotrophin receptors, including TrkA and p75 NTR , 30,32) but our understanding of the mechanisms involved in the control of neuronal differentiation and outgrowth by RA remains limited.…”
Section: Virtual Cloning Of Gde2 and It's Physiological Roles Inmentioning
confidence: 99%
“…[12][13][14] In addition, retinoids can also downregulate the expression of certain genes such as N-MYC, concurrent with the arrest of cell proliferation. 11,5,16 Elucidating the mechanisms behind the differentiation of neuroblastoma cells is therefore of clinical importance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, retinoic acid downregulates Rae1, hence facilitating APC Cdh1 -mediated Skp2 degradation leading to the arrest of cell cycle progression and neuroblastoma differentiation. Oncogene (2008) 27, 3339-3344;doi:10.1038/sj.onc.1210987;published online 21 January 2008 Keywords: retinoic acid; Rae1; Cdh1; Skp2; p27; neuroblastoma It is well established that the vitamin A metabolite, all-trans-retinoic acid (RA) plays important roles in the development of the mammalian nervous system, including neural patterning and development of cerebral structure (Maden, 2002;Clagett-Dame et al, 2006). In certain neural progenitor niches of the postnatal brain, RA downregulates cellular proliferation and promotes neurogenesis (Matthay, 1999), an observation that has raised the interest of RA in neurorepair strategies for some human neuroblastomas (Reynolds et al, 2003).…”
mentioning
confidence: 99%